Integrating civil liberty and the ethical principle of autonomy in building public confidence to reduce COVID-19 vaccination inequity in Africa - Marilyn A. Couch; Patrick D. M. C. Katoto; Samuel Fikiri Cinini; Charles S. Wiysonge (Taylor & Francis Group, 2023)
Concerns regarding the safety of COVID-19 vaccination have caused hesitancy and lowered uptake globally. While vaccine hesitancy is documented globally, some continents, countries, ethnic groups and age groups are disproportionately affected, resulting in significant global inequities. To date, Africa has the lowest COVID-19 coverage globally, with only 22% of its population completely vaccinated. It might be argued that the difficulty with COVID-19 vaccine acceptance in Africa was triggered by the anxiety created by misinformation on social media platforms, particularly with the misinformation regarding depopulating Africa, given the significance of maternity in the continent. In this work, we examine numerous determinants of poor vaccination coverage that have received little attention in primary research and that may need to be considered by various stakeholders engaged in the COVID-19 vaccine strategy at the national and continental levels. Our study also emphasizes the importance of a multidisciplinary team when introducing a new vaccine, for people to trust that the vaccine is truly helpful to them and to be convinced that immunization is, all things considered, worthwhile.